Tagging of RPS9 as a tool for ribosome purification and identification of ribosome-associated proteins - Jovanovic, Bogdan; Schubert, Lisa; Poetz, Fabian; Stoecklin, Georg (Archives of biological sciences, 2021)
Ribosomes, the catalytic machinery required for protein synthesis, are comprised of 4 ribosomal RNAs and about 80 ribosomal proteins in mammals. Ribosomes further interact with numerous associated factors that regulate their biogenesis and function. As mutations of ribosomal proteins and ribosome-associated proteins cause many diseases, it is important to develop tools by which ribosomes can be purified efficiently and with high specificity. Here, we designed a method to purify ribosomes from human cell lines by C-terminally tagging human RPS9, a protein of the small ribosomal subunit. The tag consists of a flag peptide and a streptavidin-binding peptide (SBP) separated by the tobacco etch virus (TEV) protease cleavage site. We demonstrate that RPS9-Flag-TEV-SBP (FTS) is efficiently incorporated into the ribosome without interfering with regular protein synthesis. Using HeLa-GFP-G3BP1 cells stably expressing RPS9-FTS or, as a negative control, mCherry-FTS, we show that complete ribosomes as well as numerous ribosome-associated proteins are efficiently and specifically purified following pull-down of RPS9-FTS using streptavidin beads. This tool will be helpful for the characterization of human ribosome heterogeneity, post-translational modifications of ribosomal proteins, and changes in ribosome-associated factors after exposing human cells to different stimuli and conditions.